Insan Paripurna As the Final Goal of Islamic Education - Akbar, Akbar Tanjung; Shidiq, Sapiudin; Suparto; Nata, Abuddin (Universitas Islam Negeri Raden Intan Lampung, 2025)
Islamic education in Indonesia faces significant challenges related to moral decadence among students and alumni. Although education has successfully produced intelligent, skilled, and independent individuals, spiritual and moral aspects are often neglected. This article discusses the concept of Insān Paripurna in Islamic education and its relevance to the goals of national education in Indonesia. This research uses a qualitative approach with a desk study to analyze related literature. Insān Paripurna is defined as a human being who achieves perfection by actualizing his spiritual, intellectual, and moral potential, which is reflected in a good and balanced character. Islamic education aims to shape individuals who are not only intelligent but also possess deep spiritual awareness, thus aligning with the constitutional goals of national education. This research finds that Islamic education has the potential to realize Insān Paripurna in line with the goals of national education, namely to create people who are faithful, have noble character, and are responsible as caliphs on earth. Therefore, synergy between Islamic education and national education is needed to achieve these goals holistically.